2017
DOI: 10.3144/expresspolymlett.2017.84
|View full text |Cite
|
Sign up to set email alerts
|

Simple synthesis of porous melamine-formaldehyde resins by low temperature solvothermal method and its CO2 adsorption properties

Abstract: Abstract.A simple and environmentally-friendly approach for the preparation of porous melamine-formaldehyde resins (PMFRs) was developed by using low-boiling-point solvents, such as water, as pore-forming agent. With using dimethyl sulfoxide (DMSO) and low-boiling solvents cosolvent method, PMFRs with a high specific surface area and well-defined pore structure can be synthesized at a low reaction temperature of 140°C for a short reaction duration in 20 hours, which can replace the conventional methods that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…Nevertheless, both materials are characterized by a polymeric structure consisting of a network of melamine rings interconnected by both ether and methylene linkages (Scheme ) with abundant triazine, primary, secondary, and tertiary amine sites, which can act as potential sites for CO 2 activation (Table and Figures and ). To summarize our results, it can be concluded that the S-free porous melamine-formaldehyde materials (MMFR and MMFR250) obtained by the template-free and organosolvent-free route exhibit a mesoporous structure with large amounts of uniformly distributed basic N-sites, which closely resemble the templated and solvothermal-templated porous melamine polymers reported in earlier works. With advantages such as simple synthesis, low cost, high specific surface area (>300 m 2 /g), large mesopores (>20 nm), abundance of N (basic) sites, and good thermal stability ( T onset ∼300 vs 200 °C), these polymeric materials are potential catalysts for CO 2 activation and the production of cyclic carbonates from CO 2 and epoxides.…”
Section: Results and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Nevertheless, both materials are characterized by a polymeric structure consisting of a network of melamine rings interconnected by both ether and methylene linkages (Scheme ) with abundant triazine, primary, secondary, and tertiary amine sites, which can act as potential sites for CO 2 activation (Table and Figures and ). To summarize our results, it can be concluded that the S-free porous melamine-formaldehyde materials (MMFR and MMFR250) obtained by the template-free and organosolvent-free route exhibit a mesoporous structure with large amounts of uniformly distributed basic N-sites, which closely resemble the templated and solvothermal-templated porous melamine polymers reported in earlier works. With advantages such as simple synthesis, low cost, high specific surface area (>300 m 2 /g), large mesopores (>20 nm), abundance of N (basic) sites, and good thermal stability ( T onset ∼300 vs 200 °C), these polymeric materials are potential catalysts for CO 2 activation and the production of cyclic carbonates from CO 2 and epoxides.…”
Section: Results and Discussionsupporting
confidence: 66%
“…Thus, developing a cost-effective (template-free and organosolvent-free) approach for fabrication of porous melamine-formaldehyde resins is highly desirable. While there are several publications demonstrating the application of porous poly-melamine-formaldehyde resins for CO 2 capture, , only one report could be found describing the catalytic use of a melamine-formaldehyde resin for cyclic carbonate production . However, the reported material was modified with zinc and exhibited catalytic activity only in the presence of tetrabutylammonium bromide (TBAB) as a co-catalyst, and the activity of porous poly-melamine-formaldehyde resin itself was negligible .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile the peaks locating between 40 and 70 ppm could be assigned to the sp 3 carbon of aminal groups. 38,39 Furthermore, the signals appearing in the range from 100 to 157 ppm could be assigned to the sp 2 carbon of residual aldehydes. So it is confirmed by FTIR and 13 C-NMR spectra that the aminal-linked polymers was successfully constructed.…”
Section: Structure Characterization Of Paopsmentioning
confidence: 99%
“…Nevertheless, the longer PEI chain carried more NH 2 groups onto the foam surface, and the CO 2 uptake was still more than its low‐molecular‐weight counterparts, because CO 2 chemisorption uptake was mainly determined by amine content. As a result, the highest capturing capacity of PAA‐PEI (10000) reached to 5.91 mmol g −1 , which was greater than the report capacity of 2.37 mmol CO 2 g −1 of porous melamine‐formaldehyde resins and 13.86 mg CO 2 g −1 of BTC‐based metal–organic frameworks …”
Section: Resultsmentioning
confidence: 99%